The Influence of Transformational Leadership and Organizational Justice on Intention to Stay with Mediated Work Engagement - Saputra, Gregorius Deri; Giriati; Hasanudin; Shalahuddin, Ahmad (Ilomata International Journal of Management, 2025)
Good leadership and organizational justice will increase the desire to stay in the company, and job attachment will reinforce this. This study analyzes the effect of transformational leadership and organizational justice on intention to stay, mediated by job attachment. This study uses quantitative methods, with a population of CU employees in West Kalimantan and a sample of 202 people taken through probability sampling with a purposive sampling technique. Data analysis tools using Smart PLS 4.0. used to process data and perform analysis steps. The results showed that transformational leadership does not directly affect the intention to stay but significantly affects job attachment. Job attachment also mediates the relationship between transformational leadership and organizational justice on intention to stay.